PENGARUH LINGKUNGAN KERJA DAN INOVASI TERHADAP KEPUASAN KERJA KARYAWAN MILENIAL DI PT XYZ DENGAN PENGEMBANGAN KARIR SEBAGAI VARIABEL INTERVENING - Octora, Sophia Dwiyanti; Priambodo, Ervin Agung; WS, Paidi (Journal of Management and Leadership, 2023)
Employees are an important company asset who have quality work competencies to provide the best performance to support company programs. In practice, the Human Capital (HC) team has a competency improvement program that requires motivation from employees as an internal factor so that the program can run effectively. Work motivation is affected by a variety of factors such as salary, work environment, job security, relationships with coworkers, awards, and so on. This influences whether an employee is satisfied with his or her job. The proportionate stratified random sampling approach was utilized, which is a sampling methodology for populations with mixed or variable features, and the data in this study uses a quantitative approach. The population is millennial employees at PT XYZ with a total of 139 millennial employees. The data was collected by distributing a questionnaire with 28 closed questions and response options indicating how strongly respondents agreed or disagreed with the questions posed. The results show it is possible to conclude that the millennial employees at PT XYZ have a level of job satisfaction that is influenced by work environment factors, innovation, and career development factors that can mediate changes in the level of job satisfaction. This finding could be an overview of benchmarks for management in departments, so that job satisfaction obtained by employees does not become a saturation point but becomes a driving force to improve their performance in this company continuously.